Development of Multimedia-Based Learning Media for Recognizing Wild Animals for Early Childhood - Sabilla, Carissa Trissiasal; Luthfy, Perdana Afif; Sagala, Anita Chandra Dewi (UPI Kampus Cibiru, 2024)
Technology is critical in everyday life today, and many people use it to do various things, including education, to absorb information quickly and efficiently. However, with technological advances, many teachers still use guidebooks as a learning medium, sometimes dull children. This research aims to create exciting learning media for young children about recognizing wild animals. This media is expected to make children active and happy to learn. In addition, this research will guide educators in using multimedia media to make learning more enjoyable for children. Analysis, design, development, implementation, and evaluation are the five steps in the development or RD model. Validation questionnaires were given to the validators, teachers, and students of this study. Initial field trials of the product obtained an average of 65.54%, which is included in the feasible category. The second field trial of the product experienced a significant increase with an average of 95%, which was in the